Reducing the motion of laser spot using hollow wall design in hohlraum - Lu Zhang; Longfei Jing; Zhiwei Lin; Liling Li; Tuo Zhu; Xin Hu; Jin Li; Xin Li; Lifei Hou; Xingsen Che; Huabing Du; Longyu Kuang; et al. (Nuclear Fusion)
A longer pulse, lower adiabat drive in a low gas-fill hohlraum is an inertial confinement fusion design with potential higher gain, but has challenges such as the less tamped wall plasma. Thus, it is necessary to alter the laser spot regions to control low-mode drive asymmetry when using such laser pulses. The hollow wall is designed [Vandenboomgaerde et al 2018 Phys. Plasmas 25 012713] and has been demonstrated with experiments to be effective in holding back the gold bubble expansion [Depierreux et al 2020 Phys. Rev. Lett . 125 255 002]. This paper presents experimental and simulation results demonstrating that hollow wall hohlraums effectively reduce laser spot motion. Experiment results indicate that the laser spot position in hollow wall hohlraum moves less than that in classical solid hohlraum, similar data are obtained by 2D simulation. This reduction in motion is beneficial for improving P4 drive asymmetry.